IgLON5 autoimmunity in a patient with Creutzfeldt–Jakob disease: case report and review of literature - Li, Xiaofeng; Chen, Yimin; Zhang, Le; Zhang, Wei; Li, Bin; Baizabal-Carvallo, José Fidel; Song, Xingwang (Frontiers in Neurology, 2024)
Objective: We present the case of a patient with clinical and imaging features of sporadic Creutzfeldt-Jakob disease (sCJD) and positive IgLON5 antibodies (Abs) in the serum and CSF.Case Report: A 66-year-old Chinese man presented to the hospital with a stroke-like episode, followed by rapidly progressive cognitive decline, mutism and parkinsonism. MRI showed a cortical ribboning sign in diffusion weighted MRI, periodic triphasic waves with slow background in EEG, and positive protein 14-3-3 in CSF. There were matching IgLON5 Abs in the serum and CSF. A literature review showed positive autoimmune encephalitis Abs or autoimmune inflammatory disease in between 0.5% and 8.6%, among patients with clinical suspicion of CJD. Most commonly antivoltage-gated potassium channel (VGKC)-complex and anti-N-methyl-D-aspartate receptor (NMDAR) Abs; however, IgLON5 autoimmunity in CJD has been rarely reported. This is an intriguing association as both conditions have been associated with brain deposits of phosphorylated tau-protein.Abs may be observed in patients with diagnosis of CJD; it is unknown whether a synergistic effect of IgLON5 Abs with CJD exists, increasing neurodegenerative changes.